Pre-Amplification of Cell-Free DNA: Balancing Amplification Errors with Enhanced Sensitivity - Wei Yen Chan; Ashleigh Stewart; Russell J. Diefenbach; Elin S. Gray; Jenny H. Lee; Richard A. Scolyer; Georgina V. Long; Helen Rizos (Biomolecules)
Circulating tumour DNA (ctDNA) is a promising biomarker for personalised oncology. However, its clinical utility is limited by detection sensitivity, particularly in early-stage disease. T-Oligo Primed Polymerase Chain Reaction (TOP-PCR) is a commercial amplification approach utilising an efficient “half-adapter” ligation design and a single-primer-based PCR strategy. This study evaluated the clinical value and application of cell-free DNA (cfDNA) pre-amplification. cfDNA amplification with TOP-PCR preserved DNA size profiles and resulted in a 22 bp size increase due to the half-adaptor ligation. Gene target amplification rates varied, showing lower efficiency for the GC-rich TERT promoter amplicon and higher efficiency for the BRAF and TP53 amplicons. Optimised pre-amplification (20 ng cfDNA input and 5–7 cycles of PCR) enhanced ctDNA detection sensitivity and expanded sample availability for the detection of multiple tumour-informed mutations. Importantly, PCR errors emerged in pre-amplified cfDNA samples, underscoring the necessity for negative controls and the establishment of stringent mutation positivity thresholds.